PENGGUNAAN CONCEPTUAL CHANGE TEXT BERBANTUAN ALAT PERAGA UNTUK MEREMEDIASI MISKONSEPSI MATERI FLUIDA DINAMIS DI SMA - Metal, Step; Sitompul, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract          This study aims to determine the effectiveness of the use of conceptual change text assisted teaching aids in remediating students' misconceptions about dynamic fluid in Nanga Mahap 1 State High School. This study was a pre-experimental design with one group pretest-posttest design. The sample is 30 students of class XI MIPA 2 totaling 30 students selected by intact group. The data collection instrument uses multiple choice diagnostic tests without reason. Based on the results of data analysis obtained the findings, as follows: (1) There is a significant conceptual change (itung_count ^ 2 = 38,025; df = 1; α = 0,05) after being given remediation learning; (2) The level of remediation effectiveness is classified as moderate (DQM = 45.5%); (3) There is no significant conceptual change (itung_count ^ 2 = 0.26; df = 1; α = 0.05) after a certain period of time since remediation learning is given. Based on these results, it is expected that conceptual change text assisted by teaching aids can be used as an alternative to correct misconceptions.Keywords: Remediation, misconception, conceptual change text, props, dynamic fluid